Resistance to Colletotrichum lindemuthianum isolates from middle America and Andean South America in different common bean races - Pastor Corrales, Marcial A.; Otoya, María Mercedes; Molina Castaneda, A (Scientific Societies, 1995)
A total of 20,144 common bean (Phaseolus vulgaris) accessions were evaluated in the field at CIAT-Popayan, Colombia, with a mixture of local isolates of the anthracnose pathogen, Colletotrichum lindemuthianum. Of these, 4,939 (24.5%) accessions were resistant, and another 4,410(2l .9%) showed an intermediate reaction between resistant and susceptible. These accessions were then inoculated at the seedling stage in the screenhouse at the same site with the same mixture of isolates. The 3,778 accessions showing resistance were subsequently challenged in a greenhouse at the seedling stage, with a mixture of isolates from Middle America and separately with a mixture from Andean South America. Resistance to all isolates was found in 1,270 accessions, and of these, 350 (1.7% of total) were immune. These sources of resistance included representatives from all six races of cultivated common bean and showed variation for growth habit, maturity, seed color and size, adaptation traits, and geographical origin. Also, 68 resistant accessions were wild common beans from Middle America and Andean South America.